DESIGN THINKING AS A STRATEGY IN FACING VUCA - Agra Fadhiila Tamara; Alby Silmi Maulidan; Ali Akbar Alkatili; Fakhrizal Labib Musyaffa; Nadiyah Husniyah (Indonesian Journal of Digital Business, 2021)
The purpose of this literary studies is to explain how was the design thinking as a strategy that can be used for deal with this VUCA conditions. The type of this research is nature qualitative by taking sources through literature studies. Activities that can be carried out in the context of implementing design thinking in every business activity are separating facts from opinions, listening and understanding a lot, gathering facts from various sources, as well as gathering and evaluating arguments.Keywords: Design thinking, VUCA, business.